South Africa’s Youth Unemployment Dilemma: Whose Baby is it anyway? - Meyer, Natanya (Journal of Economics and Behavioral Studies, 2017)
Youth unemployment is a major concern to various different countries, including South Africa, which ranked fourth-worst in the global youth unemployment ratings in 2013 and 2014reaching rates of more than 50 percent. Entrepreneurship development and increased employability through appropriate skills development have been considered as possible solutions to this growing problem. The aim of this study is to determine perceptions of students pertaining their entrepreneurial outlook and perceived employability. Validated Entrepreneurship- and Employability Scales were used to determine entrepreneurial outlook and perceived employability perception. A total of 293 students from a South African University participated in this study. Data were analyzed using descriptive statistics, histograms, Pearson correlation, MANOVA and ANOVA. The findingsof this studyshow that student’sperceptions indicated that if they haveamore entrepreneurial outlook, it could strongly increase their employability. They also do not think that after the completion of their degrees that they would be more employable. A significance difference was found between year level of study, race, age, and perception of entrepreneurial outlook and employability variables of the students.They seem to have a realistic view when it comes to the risk of possible unemployment for some time after graduation. Based on these findings, it is suggested that introducing entrepreneurship training and employability programs (skills development) to students during the completion of their higher education career, could assist in the reduction of youth unemployment in South Africa.